Health and Health Inequality during the Great Recession: Evidence from the PSID - Chenggang Wang; Huixia Wang; Timothy J. Halliday (Institute of Labor Economics (IZA), 2017)
We estimate the impact of the Great Recession of 2007–2009 on health outcomes in the United States. We show that a one percentage point increase in the unemployment rate resulted in a 7.8–8.8 percent increase in reports of poor health. Mental health was also adversely impacted and reports of chronic drinking increased. These effects were concentrated among those with strong labor force attachments. Whites, the less educated, and women were the most impacted demographic groups.
Keywords: I0; I12; I14; 330; health outcomes; health behaviors; Great Recession; inequality